1998
DOI: 10.4065/73.3.246
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Due to Endogenous Testosterone Production in a Woman

Abstract: Obstructive sleep apnea (OSA) is a common condition characterized by snoring, recurrent episodes of cessation of breathing (obstructive apneas), disrupted sleep, and excessive daytime somnolence. Associated serious complications are hypertension, increased risk of heart disease, stroke, and increased susceptibility to industrial and motor vehicle accidents. OSA is considerably more common in men than in women. In postmenopausal women, the incidence of OSA increases. These factors suggest that reproductive horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Those observations suggest that decrease of androgens in ageing males alleviates snoring, whereas menopause-induced oestrogen and progesterone deficiency and increased androgenicity continue to aggravate snoring in postmenopausal females. In a lean, 70-yr-old female, a testosteroneproducing tumour caused sleep apnoea, which disappeared after removal of the tumour [142]. Exogenous testosterone induces sleep apnoea and even alters the upper airway dimensions in females [143].…”
Section: Androgensmentioning
confidence: 99%
“…Those observations suggest that decrease of androgens in ageing males alleviates snoring, whereas menopause-induced oestrogen and progesterone deficiency and increased androgenicity continue to aggravate snoring in postmenopausal females. In a lean, 70-yr-old female, a testosteroneproducing tumour caused sleep apnoea, which disappeared after removal of the tumour [142]. Exogenous testosterone induces sleep apnoea and even alters the upper airway dimensions in females [143].…”
Section: Androgensmentioning
confidence: 99%
“…These findings support a protective effect of female sex hormones on some of the pathogenetic factors related to SDB. Conversely, increased testosterone levels have been associated with exacerbation or occurrence of obstructive sleep apnoea in a few adult male and female cases [15,16]. It has been speculated that testosterone may influence neuromuscular control of the upper airway and the central pattern of body fat distribution that have been related to SDB in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that menopause is a risk factor for SDB and that hormone replacement therapy modifies this risk [14]. Conversely, treatment with testosterone has been reported to cause obstructive sleep apnoea in males [15]. In addition, a case of a nonobese female with clinically significant obstructive sleep apnoea and a benign testosterone-producing ovarian tumour that resolved after successful removal of the tumour, along with normalisation of testosterone levels, has been reported [16].…”
mentioning
confidence: 99%
“…Testosterone, in fact, is one of the main factors influencing AHI in men. Exogenous administration of testosterone increases AHI in men and is capable of inducing OSA in women [6].…”
Section: Physiopathogenetic Mechanism Of Sdb In Pregnant Womenmentioning
confidence: 99%